1999
DOI: 10.1097/00007890-199905150-00473
|View full text |Cite
|
Sign up to set email alerts
|

Factors in Older Cadaveric Organ Donors Impacting on Renal Allograft Outcome

Abstract: Transplantation of renal allografts (RA) from older donors has become more common, despite conflicting data on outcome between reports from large series versus individual centres. Factors other than donor age per se may contribute to RA outcome. 
The outcome of RA procured from 114 older donors over 55 yr of age in NSW, between 1990 and 1997, was analysed. Corresponding donor factors, including demographics, medical history, inotrope use, major hypotension and findings at procurement, were also analysed. 
Of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
2
5
0
1
Order By: Relevance
“…As previously reported, we found that a donor history of hypertension was associated with a worse graft outcome (7,(29)(30)(31). The presence of hypertension is one of the most relevant factors to consider in the evaluation of the donor, as it underlies the crucial importance of evaluating arterial disease in elderly potential donors (7).…”
Section: Validationsupporting
confidence: 51%
“…As previously reported, we found that a donor history of hypertension was associated with a worse graft outcome (7,(29)(30)(31). The presence of hypertension is one of the most relevant factors to consider in the evaluation of the donor, as it underlies the crucial importance of evaluating arterial disease in elderly potential donors (7).…”
Section: Validationsupporting
confidence: 51%
“…Extensive atheroma of the aortorenal arterial vasculature was the most common cause for discardment of potential renal allografts during the control period. This mirrors our previously reported experience with older cadveric RA donors 7 . However, during the biopsy‐protocol period, RA biopsy findings taken in consideration with other factors became the most common cause for RA discardment in 8/24 (33%) cases.…”
Section: Discussionsupporting
confidence: 86%
“…Donor factors influence initial graft function and survival (5)(6)(7)(8). In addition to donor age (9) and mode of brain death (10), other influential donor parameters include gender (11), whether the donor heart is beating (12), hypertension, and cardiovascular disease (13,14). The increased survival of kidney allografts from living donors compared with cadaver allografts with similar HLA mismatches is probably related, at least in part, to injury from brain death (15).…”
mentioning
confidence: 99%